Alkaloids Profiling of Fumaria capreolata by Analytical Platforms Based on the Hyphenation of Gas Chromatography and Liquid Chromatography with Quadrupole-Time-of-Flight Mass Spectrometry - María del Mar Contreras; Noureddine Bribi; Ana María Gómez-Caravaca; Julio Gálvez; Antonio Segura-Carretero (International Journal of Analytical Chemistry)
Two analytical platforms, gas chromatography (GC) coupled to quadrupole-time-of-flight (QTOF) mass spectrometry (MS) and reversed-phase ultrahigh performance liquid chromatography (UHPLC) coupled to diode array (DAD) and QTOF detection, were applied in order to study the alkaloid profile of Fumaria capreolata. The use of these mass analyzers enabled tentatively identifying the alkaloids by matching their accurate mass signals and suggested molecular formulae with those previously reported in libraries and databases. Moreover, the proposed structures were corroborated by studying their fragmentation pattern obtained by both platforms. In this way, 8 and 26 isoquinoline alkaloids were characterized using GC-QTOF-MS and RP-UHPLC-DAD-QTOF-MS, respectively, and they belonged to the following subclasses: protoberberine, protopine, aporphine, benzophenanthridine, spirobenzylisoquinoline, morphinandienone, and benzylisoquinoline. Moreover, the latter analytical method was selected to determine at 280 nm the concentration of protopine (9.6 ± 0.7 mg/g), a potential active compound of the extract. In conclusion, although GC-MS has been commonly used for the analysis of this type of phytochemicals, RP-UHPLC-DAD-QTOF-MS provided essential complementary information. This analytical method can be applied for the quality control of phytopharmaceuticals containing Fumaria extracts currently found in the market.